Surface coated red phosphors with silica nanoparticles and silica nanocomposites: performance modifications - Phuc Dang Huu; Tri-Vien Vu (Universitas Ahmad Dahlan, 2022)
Surface coverings using nanomaterials of silica nanoparticles and poly (methyl methacrylate) – abbreviated “PMMA-silica nanomaterials” – are introduced to the Y2O2S:Eu3+ phosphor through four distinct approaches. The objective is to enhance Y2O2S:Eu3+ phosphorescence and prolonged sustainability. Using immerse-daubing along with sol-gel approach (Stober way), it is possible to have Y2O2S:Eu3+ phosphors covered with relatively-monodisperse nano-silica particles (5 nm). To create the silica nano-crystals employed in the coating process of phosphors, we carry out concurrently hydrolysis and condensation procedures to develop the formation and basic polymerization utilizing poly (1-vinyl-2-pyrrolidone). The surface coating layer for Y2O2S:Eu3+ spheres, which comprises polymethyl methacrylate (PMMA)-silica nanocomposites, can be formed in two ways: by combining silica nanogranules with methyl methacrylate (MMA) monomer as well as through subjecting MMA to tetraethyl orthosilicate (Si(OC₂H₅)₄) chemical compound. The latter approach demonstrated is considered the highest augmentation in phosphorescence and prolonged sustainability for Y2O2S:Eu3+ spheres. Specifically, when using the second approach to get PMMA-silica phosphor coating, Y2O2S:Eu3+ exhibited a 5-percent increase in the phosphorescent intensity, compared to untreated phosphors. Contrary to a drop in cathode phosphorescence (CP) output and a rising bombardment duration for exposed phosphor, the latter technique produces a practically constant CP energy with PMMA-silica nanocomposite covered phosphors.